Pakistan Cotton Biophysical Survey, 2013 - International Food Policy Research Institute; Innovative Development Strategies; National Institute of Genomics and Advanced Biotechnology, National Agricultural Research Center; University of Agriculture, Faisalabad (International Food Policy Research Institute, 2016)
To study the efficiency of genetically modified cotton markets in Pakistan, a series of household surveys were designed and implemented in 2013. Aside from the four rounds of household surveys, the research team also designed a biophysical survey. The purpose of the biophysical survey was to measure the presence and expression level of Cry protein in farmers’ fields. The plot selected to collect tissue samples to be tested was the “main” cotton plot identified in the household surveys implemented in 2013-14. The collection, tests, and analysis of the cotton tissue (leaves and bolls) was led by the University of Agriculture, Faisalabad (UAF), and the National Institute for Genomics and Advanced Biotechnology (NIGAB), Islamabad, in collaboration with International Food Policy Research Institute (IFPRI), and Innovative Development Studies. Two different tests were carried out. The first one was the strip test that test for the presence or absence of the Cry1Ac protein. The second was the enzyme-linked immunosorbent assay (ELISA) that quantifies the expression level of this protein. Two rounds of tests were conducted, the first at approximately 70 days after sowing (DAS) and the second at approximately 120 DAS. The resultant dataset combines information from 593 sampled households with corresponding plant tissue diagnostics from 70 DAS, as well as information from 589 sampled households with corresponding diagnostics from 120 DAS.